(untitled) (Research, Society and Development, 2021)
Introduction: Violence against women is characterized as a public health matter, and as a violation of women’s human rights, which can negatively affect the physical, mental, sexual and reproductive health of women and it is practiced especially by the intimate partner. Nursing assistance leads care facilitate the care process mediated by interventions directed to the patient’s overall health. Objective: To identify evidence in national and international scientific literature on primary nursing care for women victims of violence perpetrated by an intimate partner. Method: Integrative review performed in the Latin American and Caribbean Health Science Literature databases in virtual health library and Web of Science, via CAPES Journal Portal. Original studies were selected, without language or temporal limitations, which met the research question. The studies were submitted to reading by two independent reviewers and after data extraction, organized in a synoptic table. Results: Most part of the articles were searched in the virtual health library database, the sample of 13 articles were selected in full about violence perpetrated against women by intimate partners, the studies raised questions about nursing applied to alternative strategies that contemplate the psychological health of women who have suffered violence. Therefore, nursing interventions were developed that sought to identify this phenomenon and its correct management in order to minimize physical and psychological impacts on affected women. Conclusion: The studies revealed nursing intervention strategies for women victims of especially physical and psychological violence and pointed to the need for training of family health strategy teams, emphasizing comprehensive and humanized care among these victims.